Ambiguous loss : learning to live with unresolved grief - Boss, Pauline (Cambridge, Mass. : Harvard University Press, 1999)
Ofrece consejos para familias de como tratar con la pena que ocurre cuando uno ser amado es perdido en circunstancias inciertas, como en el caso de un soldado desaparecido en combate, o un paciente aquejado con Alzheimer.
Frozen grief -- Leaving without goodbye -- Goodbye without leaving -- Mixed emotions -- Ups and downs -- The family gamble -- The turning point -- Making sense out of ambiguity -- The benefit of a doubt.
Includes bibliographical references (pages 143-151).
Print version record.
English.
Added to collection customer.56279.3
Keywords: Loss (Psychology); Grief; Families -- Psychological aspects; Interpersonal relations; Death; Death; Grief; Interpersonal Relations; Family -- psychology; Perte (Psychologie); Chagrin; Familles -- Aspect psychologique; Relations humaines; Mort; grief; deaths; PSYCHOLOGY -- Mental Health; PSYCHOLOGY -- General; Death; Families -- Psychological aspects; Grief; Interpersonal relations; Loss (Psychology); Verlust; Psychologie; Verlies (psychologie); Rouw; Gezinsrelaties; absence; addiction; child; complicated grieving; death; depression; frozen; lack control; melancholia; parent; relationship; stress; therapy